Computer-based assessment of problem solving. - Baker, E. L.; Mayer, R. E. (Computers in Human Behavior)
Part of a special issue on computer-based performance assessment of problem solving. The writers examine the components required to assess student problem solving in technology environments. They discuss the purposes of testing and demonstrate, using an example, the difference between retention and transfer. They define and analyze problem solving and also investigate techniques and standards for measuring the quality of student understanding. They contend that the purposes of assessment can, with appropriate cognitive demand frameworks and key standards, be integrated into a coherent technology-based system of assessment that can be used in both public and classroom discourse.